2004
DOI: 10.1099/mic.0.26674-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of the hprT–ftsH locus in Staphylococcus aureus

Abstract: The roles of two adjacent genes in the Staphylococcus aureus chromosome with functions in starvation survival and the response to stressful conditions have been characterized. One of these, hprT, encoding a hypoxanthine-guanine phosphoribosyltransferase homologue, was initially identified in a transposon mutagenesis screen. Mutation of hprT affects starvation survival in amino-acid-limiting conditions and the ability of S. aureus to grow in high-salt concentrations. Downstream of hprT is ftsH, which encodes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 41 publications
2
41
0
1
Order By: Relevance
“…Recently, it was shown that mutation of cysM encoding cysteine synthase caused increased sensitivity of S. aureus to tellurite, hydrogen peroxide, acid, and diamide and also significantly reduced the ability of S. aureus to recover from starvation in amino acid-or phosphate-limiting conditions, indicating that cysteine has a role in the S. aureus oxidant stress response and survival mechanisms (12). Also of interest, mutation of a membrane-bound, ATPand Zn 2ϩ -dependent "AAA-type" protease gene in S. aureus led to pleiotropic defects, including slower growth, sensitivity to salt, acid, methyl viologen, and potassium tellurite stresses, and reduced survival in amino acid-or phosphate-limiting conditions (13). Thus, these data provide further support for the hypothesis that the reduced ⌬⌿ and ATP of the SCVs play a role in the susceptibility of these variants to selenite, tellurite, and nitrite.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that mutation of cysM encoding cysteine synthase caused increased sensitivity of S. aureus to tellurite, hydrogen peroxide, acid, and diamide and also significantly reduced the ability of S. aureus to recover from starvation in amino acid-or phosphate-limiting conditions, indicating that cysteine has a role in the S. aureus oxidant stress response and survival mechanisms (12). Also of interest, mutation of a membrane-bound, ATPand Zn 2ϩ -dependent "AAA-type" protease gene in S. aureus led to pleiotropic defects, including slower growth, sensitivity to salt, acid, methyl viologen, and potassium tellurite stresses, and reduced survival in amino acid-or phosphate-limiting conditions (13). Thus, these data provide further support for the hypothesis that the reduced ⌬⌿ and ATP of the SCVs play a role in the susceptibility of these variants to selenite, tellurite, and nitrite.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of some of these genes, for instance, qoxB (Fig. 5C), SAV0862 (1), clpx (15), clp (15), sodA (24), srtA (22), ftsH (28), srrA (42), saeR-saeS (27), sarZ (7), sarA (4), sigB (21), rsbU (21), sucB (35), and dnaD (11), has been shown to result in attenuated virulence of S. aureus in vivo. Thus, the dramatic virulence attenuation of purA and purH mutant strains is most likely due to a combination of several effects, including nutrient limitation, energy metabolism, stress response, and altered (34).…”
Section: Discussionmentioning
confidence: 99%
“…Of the three, ClpP appears to have the greatest impact in shaping the S. aureus proteome (14), and when disrupted, it causes significant defects in growth, survival, virulence gene expression, and cell wall maintenance (15,16). FtsH has a modest role in regulating growth, stress resistance, starvation survival, and pathogenicity (17), but with a putative localization to the inner membrane, it is thought to mainly degrade membrane-bound targets. Very little is known about ClpQ, in part because a ⌬clpQ mutant of S. aureus exhibits few phenotypes (18) and shows few alterations to stress responses.…”
mentioning
confidence: 99%